Effects of maternal folic acid supplementation on nuclear methyltransferase activity of adult rats subjected to an animal model of schizophrenia. Issue 5 (18th April 2021) - Canever, Lara; Varela, Roger; Mastella, Gustavo A.; Damázio, Louyse S.; Valvassori, Samira S.; Quevedo, João L.; Zugno, Alexandra I.
Abstract: Introduction: Schizophrenia is considered one of the most disabling and severe human diseases worldwide. The etiology of schizophrenia is thought to be multifactorial and evidence suggests that DNA methylation can play an important role in underlying pivotal neurobiological alterations of this disorder. Some studies have demonstrated the effects of dietary supplementation as an alternative approach to the prevention of schizophrenia, including folic acid. However, no study has ever investigated the role of such supplementation in altering the DNA methylation system in the context of schizophrenia. Objectives: The present study aims to investigate the effects of maternal folic acid supplementation at different doses on nuclear methyltransferase activity of adult rat offspring subjected to an animal model schizophrenia induced by ketamine. Methods: Adult female Wistar rats, (60 days old) received folic acid‐deficient diet, control diet, or control diet plus folic acid supplementation (at 5, 10, or 50 mg/kg) during pregnancy and lactation. After reaching adulthood (60 days), the male offspring of these dams were subjected to the animal model of schizophrenia induced by 7 days of ketamine intraperitoneal injection (25 mg/kg). After the 7‐day protocol, the activity of nuclear methyltransferase was evaluated in the brains of the offspring. Results: Maternal folic acid supplementation at 50 mg/kg increased methyltransferase activity in the frontal cortex, while 10 mg/kg increased methyltransferase activity in the hippocampus. In the striatum of offspring treated with ketamine, maternal deficient diet, control diet, and folic acid supplementation at 5 mg/kg decreased methyltransferase activity compared to the control group. The folic acid supplementation at 10 and 50 mg/kg reversed this ketamine effect. Conclusions: Maternal FA deficiency could be related to schizophrenia pathophysiology, while FA supplementation could present a protective effect since it demonstrated persistent effects in epigenetic parameters in adult offspring.